Evaluation of a set of genre based learning material based on the pedagogical proposal of genre (RAMOS, 2004) - Cardoso, Zelia Cemin (The ESPecialist, 2015)
This paper is part of a larger project – Developments of teachers and multipliers of ESP for the Brazilian technical education system - identified as ESPtec, and it aims at presenting the learning evidences of the pedagogical proposal of genre (Ramos, 2004) in the material developed by one center of the technical education system (Center B) that participated in the project.The unit presented here was developed to deal with a written genre and it was evaluated according to the pedagogical proposal of Ramos (2004). The theoretical foundations include the concept of genre according to Swales (1990), Bhatia (1993) and Martin (1984), of material development and mainly the pedagogical proposal of Ramos, 2004. The results of such evaluation indicate the learning evidences of this proposal identified in the unit developed to teach a written genre elaborated by the institution chosen for this article. The results presented in this paper may be relevant to other research studies that aim the ESP teacher’s development with focus on material development based on the concept of genre and the pedagogical proposal (Ramos, 2004).